The Power of Play: Examining the Impact of a School Yard Playground on Attitudes Toward School and Peer Relationships Among Elementary School Students in Chennai, India - Shan Lateef BS; Rhea Zahir BS; Leena Sherdil BS; Carol McCleary PsyD; Tasnuva Shafin MD, MS (SAGE Publishing, 2024)
Introduction. School environments may impact elementary school students' attachment levels to school as well as their mental and emotional well-being. Yet investments in recess/play infrastructure lag commitments to academic resources, particularly in developing countries. The main objective was to examine the impact of installing playground equipment, in the school yard, on students' attitudes toward school, peers, and the capacity to play of elementary-school children in an underserved, inner-city school in Chennai, India. Methods. A previously validated school attachment questionnaire was modified and administered to 140 and 148 students in pre- and post-playground installation, respectively. Results. For 7 out of 13 survey questions, student attitudes about their own recreational time and their attitudes toward peers significantly improved after playground installation. Conclusion. These results highlight the need for investments in play spaces, and recreational equipment may be just as important as addressing academic needs, especially among underserved children.